Unemployment and the Migration of the Romanian Labour Force. Causes and Effects - Mirela Stoian; Georgiana-Raluca Lădaru; Florian Marin (Amfiteatru Economic)
Ensuring the set of rights and freedoms that are part of the Treaty of Accession to the European Union (EU) seems to be a double-edged sword. If in 2000s, these rights and freedoms were the main catalyst for accession to the European common market, currently these rights are generating consistent disputes among the Member States (MS). Geopolitical tensions that currently exist, along with the political changes that have occurred in certain MS have fuelled pessimism and lack of confidence in the ability of the European common market and the EU to deliver smart, sustainable and inclusive growth. We reached a point in which the very elements that underpinned the common market create suspicion regarding the future of the EU. Therefore, some opinions, (especially from politics) are in favour of a restricted or controlled access to these rights and freedoms in order to maintain stability in the EU, and the framework for growth. The significant increase of xenophobia, terrorism threats, migration crisis, populism, nationalism, and the Brexit are all elements covered by the public agenda and exerting a major pressure on the organization and functioning of the EU in general, and especially on the future of the Cohesion Policy. The development scenarios for Europe have been recently publicly released for debate, and they are a consequence of the concerns about the inability of the European development model to remain competitive globally. Our analysis was aimeds at the phenomenon of migration of the Romanian labour force in the frame of the current socio-economic climate; concretely, we made an analysis of the Romanian labour market, focused on social tensions manifested at this level, and on the one hand, and on the other hand, we analysed the minimum wage in Romania and other EU member states, namely the unemployment and the factors that influence it. The information we used came from multiple sources, such as economic literature, recent studies of various national and international bodies; statistical institutes of EU member states, etc. The economic analysis of unemployment has been completed by the utilization of a multiple linear regression model. The research first proposes a set of theoretical and methodological elements and aspects related to migration in general, and to international migration, in particular. Then, the paper analyzes the specificity of the labor market in Romania, proposing a more in-depth analysis of unemployment, which also includes an econometric model. The research enumerates the variables that determine and justify, at the same time, the emigration of Romanian workers. Also, the paper presents aspects related to the administration of the labor market in Romania, the social tensions emerging on this market, and the ratio between the minimum wage and the subsistence expenses. The number of Romanian emigrants is analyzed as well, having as source the diplomatic missions of our country in the host countries, and the national statistical institutes.